Insights from establishing a high throughput viral diagnostic laboratory for SARS-CoV-2 RT-PCR testing facility: challenges and experiences - Roy Pradhan, Sanchita; Yashavarddhan, M. H.; Gupta, Ashish; Kumar, Pramod; Kumar, Anuj; Arif, Nazneen; Agrawal, Usha; Kumar, R. Suresh; Singh, Shalini (Frontiers in Public Health, 2023)
Background: The World Health Organization declared the corona virus disease (Covid-19) a global pandemic on 11th March 2020. Identifying the infected and isolating them was the only measure that was available to contain viral spread, as there were no standardized treatment interventions available. Various public health measures including vaccination have been taken to contain the spread of the virus worldwide. India a densely populated country, requires laboratories in different zones of the country with a capacity to test large number of samples and report test results at the earliest. Indian Council of Medical Research (ICMR) took the lead role in developing policies, generating advisories and formulating guidelines, establishing and approving testing centers for Covid-19 testing. With advisories of ICMR, National Institute of Cancer Prevention and Research (NICPR) established a High-throughput Viral Diagnostic Laboratory (HTVDL) for RT PCR based diagnosis of SARS CoV-2 in April 2020. HTVDL was established during the first lockdown to serve the nation in developing and adopting rapid testing procedures and to expand the testing capacity using “Real-Time PCR”. HTVDL provided its testing support to the National capital territory of Delhi and Western Uttar Pradesh, with testing capacity of 6000 tests per day. The experience of establishing a High throughput laboratory with all standard operating procedure to different challenges in a developing country like India is explained in the current manuscript which will be useful globally to enhance the knowledge on establishing a HTVDL in pandemic or non-pandemic times.